Constructive Side-Channel Analysis and Secure Design Third International Workshop, COSADE 2012, Darmstadt, Germany, May 3-4, 2012. Proceedings - Schindler, Werner; Huss, Sorin (Security and Cryptology, 2012)
This book constitutes the refereed proceedings of the Third International Workshop on Constructive Side-Channel Analysis and Secure Design, COSADE 2012, held in Darmstadt, Germany, May 2012. The 16 revised full papers presented together with two invited talks were carefully reviewed and selected from 49 submissions. The papers are organized in topical sections on practical side-channel analysis; secure design; side-channel attacks on RSA; fault attacks; side-channel attacks on ECC; different methods in side-channel analysis.